Low absorption magnesium aluminate spinel windows for high energy laser applications. Issue 19 (14th October 2014) - Villalobos, Guillermo; Bayya, Shyam; Kim, Woohong; Baker, Colin; Sanghera, Jas; Hunt, Michael; Sadowski, Bryan; Miklos, Fritz; Aggarwal, Ishwar
Abstract: Abstract : High energy laser (HEL) systems are currently being evaluated for various land, sea, and air based platforms. Some of these systems operate in or have to withstand harsh environment of sand storm, hurricane, and rain. The exit aperture on a HEL system operating in harsh environment can become the single point of failure. Current HEL systems operating in 1–2 µm wavelength use fused silica windows which are at risk of damage in the theater. Rugged window materials such as sapphire, ALON, and spinel are currently being evaluated as a potential replacement. One of the major parameters in window selection apart from its ruggedness is its absorption loss coefficient at laser wavelength. This paper reports on 3 different methods to reduce absorption loss in spinel ceramic from 100, 000 ppm/cm down to 75 ppm/cm. The results are compared with ALON and sapphire.